PEMBERDAYAAN MASYARAKAT DALAM MENCEGAH TERJADINYA NEUROPATI PERIFIER MELALUI SENAM KAKI PADA LANSIA TAHUN 2020 - Abdurrasyid, Abdurrasyid; Seipattiratu, Claudia; Pesireron, Astrid Viona; Kempa, Melty F.; Chan, Prissandi Jeri; Laisoka, Herlin Ros; Haryandasari, Devita; Husniyah, Darma; Hardiyanti, Windi (Universitas Esa Unggul, 2020)
Elderly is a process of aging with the increasing age of individuals which is marked by a decrease in the function of organs such as the brain, heart, liver and kidneys as well as an increase in the loss of active body tissue in the form of body muscles. Decreased organ function in the elderly is due to the reduced number and ability of body cells. One of the problems that occurs is peripheral neuropathy. Peripheral neuropathy is one of the microvascular complications of diseases experienced by the elderly, which occurs in the periphery and causes damage to nerve function. Damage to nerve function can affect sensory, motor, and autonomic nerves. Foot gymnastics is an activity or exercise that can be done by the elderly to prevent damage to peripheral nerves and help blood circulation in the legs. The purpose of this activity is so that the elderly can respond to the stimulus provided by the nurse, namely being able to understand and re-practice the foot exercises that have been done by the nurse. The method used in the activity was health education and demonstration of foot exercises. The sample used in community service activities was 40 elderly. The results of the activities that have been carried out are that foot exercise can reduce the occurrence of peripheral nerve damage in the elderly who suffer from peripheral neuropathy.Â Keywords: Elderly, Peripheral Neuropathy, Foot Exercise